2019
DOI: 10.3989/gya.0928182
|View full text |Cite
|
Sign up to set email alerts
|

Composition, properties, stability and thermal behavior of tamarind (<em>Tamarindus indica</em>) seed oil

Abstract: The composition, thermal stability and phase behavior of tamarind (Tamarindus indica) seed oil were analyzed to contribute to the exploration of their potential uses. The oil was extracted from the kernel of the tamarind seed with hexane, and its main physical, chemical and thermal properties were analyzed by infrared spectrometry, gas chromatography-mass spectrometry, DSC, and TGA. The results showed that the tamarind seed had a 3.76 ± 0.20% oil with a saponification index of 174.80 ± 9.87 mg KOH/g and the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…The heating curve showed a large exothermic peak at -18 °C reaching 6.2 J g -1 . This result was similar to the onset melting temperatures of tamarind seed oil was -22.2 °C (Chacón-Fernández et al, 2019). Due to the high content of polyunsaturated fatty acids in the PFSO, the crystallization and melting temperatures are very low, which gives this oil a liquid characteristic at room temperature (25 °C).…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 82%
See 2 more Smart Citations
“…The heating curve showed a large exothermic peak at -18 °C reaching 6.2 J g -1 . This result was similar to the onset melting temperatures of tamarind seed oil was -22.2 °C (Chacón-Fernández et al, 2019). Due to the high content of polyunsaturated fatty acids in the PFSO, the crystallization and melting temperatures are very low, which gives this oil a liquid characteristic at room temperature (25 °C).…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 82%
“…in DTA comprises one exothermal peak at 380.4 °C, typically from energy liberation. Chacón-Fernández et al (2019) found in tamarind seed oil a maximum decomposition temperature at ∼418 °C. For these authors, the range between 224 -510 °C correspond to the decomposition of the constituent acylglycerols of the oil.…”
Section: Infrared Spectroscopy (Ftir)mentioning
confidence: 95%
See 1 more Smart Citation
“…Figure 2 illustrates the Fourier-transform infrared (FT-IR) spectrum of cold pressed MoSO. The peaks and shoulders provide information about structure and functional groups present in the sample 27) .…”
Section: Ft-ir Spectramentioning
confidence: 99%
“…This study highlights a suitable extraction method to obtain EOs from Tamarind seeds. Evidently, the Tamarindus indica structure becomes more accessible and solubilizes to obtain essential oil units [ 13 ]. Extraction methods that will be used in this study include Soxhlet extraction and hydrodistillation using the Clevenger apparatus.…”
Section: Introductionmentioning
confidence: 99%